Pengaruh Inovasi Produk, Store Atmosphere, dan Lokasi Terhadap Motivasi Konsumen Serta Dampaknya pada Keputusan Pembelian - arum, adelia sekar (Jurnal Kompetitif Bisnis, 2020)
This research was aimed to find out the effect of product innovation, store atmosphere, and location on consumer decisions through consumer motivation to consumer of El’s Coffee Bandar Lampung. This research applies the explanatory type with quantitative approach. The population is customer of El’s Coffee Bandar Lampung. The sampling technique is accidental sampling with a sample 100 respondents. The data were obtained from questionnaire through likert scale. Analysis data using path analysis. Based on the results of the research and data analysis, store atmosphere and location has significant effect on the variable of consumer motivation level, and store atmosphere, location, and consumer motivation has significant effect on the variabel consumer decisions. The implication of the above research is means that El’s Coffee should increase customer motivation. This suggest that the effect of store atmosphere and location on consumer decisions through consumer motivation El’s Coffee Bandar Lampung.